The Effectiveness of Picture Word Inductive Model on Writing Ability in Narrative Text at Tenth Graders of MAN 1 Wonosobo - Ungu, Niken Kencono; Qathrunnada, Zanuba (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This research is motivated by the low ability of class X L students of MAN 1 Wonosobo in writing English texts, especially in writing Narrative Texts. The study aims to investigate how the Picture Word Inductive Model (PWIM) affects students' ability to write narrative texts. This study uses Classroom Action Research (CAR) as the research design. This  research was conducted by the students in class X L MAN 1 Wonosobo in the Odd Semester of the 2022/2023 Academic Year. The location of this research is MAN 1 Wonosobo. The subjects of this study are 36 students of class X L MAN 1 Wonosobo. The results show that there is an effect of the Picture Word Inductive Model (PWIM) method on student learning outcomes in writing English narrative texts in class X L MAN 1 Wonosobo. Therefore, it is suggested that English teachers apply the Picture Word Inductive Model (PWIM) in teaching writing skills